Analisis Kandungan Karbon Monoksida (CO) Pada Mesin Diesel Dan Bensin - Markus Sampe Banne (Industrial Engineering Study Program, Pattimura University, 2011)
This research studies to know monoxide carbon content at gasoline engine and diesel with revolution of the same engine. Assaying is done by using exhaust emission of gas test device to know monoxide carbon content at diesel engine Yanmar L-40 and gasoline engine endure XL. From result of assaying indicates that ever greater of revolution hence carbon content increasingly increases. At gasoline engine and addition diesel of fuel does not influence increase of percentage of monoxide carbon but at increase of revolution of this engine has been formed monoxide carbon. This thing because of existence of domination Fuel in combustion chamber so that partly fuel is not combustible causes the forming of monoxide carbon at exhaust gas. ever greater of efficiency thermal hence monoxide carbon grade increasingly increases. Thereby Monoxide carbon yielded by Diesel Engine exhaust gas Yanmar L 40 slimmer while at gasoline engine Enduro XL carbon monoxide yielded quite a lot.